Analysis Of The Impact Of Exchange Rate (Exchange) Policy And Inflation On The Composite Stock Price Index (Jci) In Indonesia In 2023 - Fitri Amaliah (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2023)
The Indonesian capital market, represented by the Jakarta Composite Stock Price Index (JCI), faces significant turmoil in 2023 triggered by global uncertainty, fluctuations in the Rupiah (USD/IDR) exchange rate, and inflation rate dynamics. The interaction of these two macroeconomic variables on the performance of the JCI in the post-pandemic context and global monetary tightening requires an in-depth analysis. This study aims to analyze the simultaneous and partial influence of exchange rates and inflation on the movement of JCI in Indonesia during the 2023 period, as well as identify which variables have the dominant influence. This study uses a quantitative approach with multiple linear regression analysis methods of monthly time-series data from January to December 2023. Secondary data was obtained from Bank Indonesia, the Central Statistics Agency (BPS), and the Indonesia Stock Exchange (IDX). Data analysis includes classical assumption tests and hypothesis tests with the help of IBM SPSS Statistics software. The results of the study show that simultaneously, the exchange rate and inflation have a significant effect on the JCI (sig. 0.000). Partially, both variables had a negative and significant effect, with the exchange rate (coefficient -0.432; sig. 0.008) having a more dominant influence than inflation (coefficient -0.298; sig. 0.047). It is concluded that the exchange rate is the dominant factor affecting the JCI in 2023. These findings imply the importance of exchange rate stabilization policies by monetary authorities and the need for investors to consider the sensitivity of the capital market to external factors in investment decision-making.